"It's Groundhog Day": Foucault's Governmentality and Crisis Discourses in Physical Education. Issue 4 (2nd October 2018) - Casey, Ashley; Larsson, Håkan
ABSTRACT: Dominant discourses in physical education research center on subject-wide crisis. This is despite repeated calls to address enduring concerns about how physical education is taught. In short, the subject seems caught in Groundhog Day (defined by Oxford Dictionaries (n.d.) as "a situation in which a series of unwelcome or tedious events appear to be recurring in exactly the same way"). This article scrutinizes this position through Foucault's lens of governmentality, which focuses particularly on power/knowledge relations and their relationship to subjectivity. Through this lens, research functions as a shaper of contemporary understanding and becomes a means for intervention by "experts." The article is structured as a conversation between authors about dominant discourses in physical education research and issues of governmentality. It argues that research approaches such as action research are framed within other power/knowledge relations and may provide a way to wake up on a new day.